2020
DOI: 10.1084/jem.20200551
|View full text |Cite
|
Sign up to set email alerts
|

Elongated neutrophil-derived structures are blood-borne microparticles formed by rolling neutrophils during sepsis

Abstract: Rolling neutrophils form tethers with submicron diameters. Here, we report that these tethers detach, forming elongated neutrophil-derived structures (ENDS) in the vessel lumen. We studied ENDS formation in mice and humans in vitro and in vivo. ENDS do not contain mitochondria, endoplasmic reticulum, or DNA, but are enriched for S100A8, S100A9, and 57 other proteins. Within hours of formation, ENDS round up, and some of them begin to present phosphatidylserine on their surface (detected by annexin-5 binding) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…A recent study discovered a new type of neutrophil membrane deposit that results from tether formation and called the deposits elongated neutrophil-derived structures (ENDS). They showed that ENDS do not contain DNA, mitochondria or endoplasmic reticulum (ER) and that they slowly degrade over time (Marki et al, 2021). Another study observed similar particles, but referred to the remnants that migrating neutrophils leave behind on the endothelium and in the interstitium of infected tracheal tissue as neutrophil 'trails' (Lim et al, 2015).…”
Section: Neutrophil Trails As Cues For Subsequent Temmentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study discovered a new type of neutrophil membrane deposit that results from tether formation and called the deposits elongated neutrophil-derived structures (ENDS). They showed that ENDS do not contain DNA, mitochondria or endoplasmic reticulum (ER) and that they slowly degrade over time (Marki et al, 2021). Another study observed similar particles, but referred to the remnants that migrating neutrophils leave behind on the endothelium and in the interstitium of infected tracheal tissue as neutrophil 'trails' (Lim et al, 2015).…”
Section: Neutrophil Trails As Cues For Subsequent Temmentioning
confidence: 98%
“…However, this may not be the only reason for neutrophil-induced successive TEM. It has been shown that neutrophils can form tethers and deposit microparticles on the endothelium (Schmidtke and Diamond, 2000;Marki et al, 2017Marki et al, , 2021). An interesting hypothesis could be that these deposits contain cues for other leukocytes to aid in their TEM.…”
Section: Neutrophil Trails As Cues For Subsequent Temmentioning
confidence: 99%
“…This may be related to a recent report which demonstrated that rolling neutrophils on the vessel wall form tethers that, when detached, form elongated neutrophil‐derived structures (ENDS). These novel types of neutrophil‐derived microparticles do not express tetraspanins but represent another specific type of EVs originating from cellular extensions (Marki et al., 2021 ).…”
Section: Association Of Protrusion Derived Evs With Cell Migrationmentioning
confidence: 99%
“…28 Notably, while tethers appear to engage in more stable interactions, at very high shear rates such as during septic conditions, they rupture from neutrophils, forming so called S100A8/A9-rich "elongated neutrophil-derived structures". 29 These structures release S100A8/A9 into the environment depending on calcium levels which may actively promote the inflammatory milieu at the endothelial surface.…”
Section: A Capturing and Rollingmentioning
confidence: 99%